Ventromedial frontal cortex mediates affective shifting in humans: evidence from a reversal learning paradigm - Fellows, Lesley K.; Farah, Martha J. (Brain (London, England : 1878), 2003)
How do the frontal lobes support behavioural flexibility? One key element is the ability to adjust responses when the reinforcement value of stimuli change. In monkeys, this ability—a form of affective shifting known as reversal learning—depends on orbitofrontal cortex. The present study examines the anatomical bases of reversal learning in humans. Subjects with lesions of the ventromedial prefrontal cortex were compared with a group with dorsolateral frontal lobe damage, as well as with normal controls on a simple reversal learning task. Neither form of frontal damage affected initial stimulus–reinforcement learning; ventromedial frontal damage selectively impaired reversal learning.